ISLAMIC PUBLIC RELATIONS THROUGH CSR: PHILANTHROPIC PRACTICES AND ICSR FRAMEWORK IN ISLAMIC BANKS OF BANGLADESH - Md. Shahidul Haque; Jamilah Ahmad (QAULAN: Journal of Islamic Communication, 2025)
Corporate Social Responsibility (CSR) of Islamic banks has a significant impact on developing customer awareness and promoting Islamic banking products and services. Islamic banks of Bangladesh are highly motivated to practice Islamic CSR as Islam encourages to ensure welfare for everyone. This study got special attention on Philanthropic CSR. Two main objectives guided the study: to analyse the Philanthropic CSR activities of Islamic banks of Bangladesh, and to propose a framework of ICSR in the Islamic banking industry. A qualitative in-depth interview was conducted with sixteen informants, including eight Heads of public relations and eight members of the Shariah secretariat of eight full-fledged Islamic banks of Bangladesh. The informants were selected using the purposive sampling. The data were collected using a semi-structured interview questionnaire. Following the six stages of thematic analysis, the researchers analyzed the data. The results show that these banks emphasize ICSR activities, particularly, philanthropic CSR by Islamic, humanitarian, educational, and Ummah building services to develop and maintain a strong relationship with their internal and external publics. The study proposes a framework for ICSR. The application of the proposed ICSR framework can contribute to CSR and Islamic banking academia, industry, and Muslim Ummah.